2018
DOI: 10.1098/rsos.172055
|View full text |Cite
|
Sign up to set email alerts
|

Testing the assumptions of the pyrodiversity begets biodiversity hypothesis for termites in semi-arid Australia

Abstract: Fire shapes the composition and functioning of ecosystems globally. In many regions, fire is actively managed to create diverse patch mosaics of fire-ages under the assumption that a diversity of post-fire-age classes will provide a greater variety of habitats, thereby enabling species with differing habitat requirements to coexist, and enhancing species diversity (the pyrodiversity begets biodiversity hypothesis). However, studies provide mixed support for this hypothesis. Here, using termite communities in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…() also noted that species diversity should be greatest with a mixture of patches at different fire frequencies as the extremes were quite different in species composition (although any effect of patch size on S was not considered). Others have observed no effect (Davis et al, ) or a negative effect (Bassett et al, ; Foster et al, ). The extent to which this fails to support intermediate P as maximizing biodiversity due to ( i ) testing an inadequate range of P , thus observing only part of the ‘hump’, ( ii ) not using a fixed reference area, thus not appreciating that increasing patch type is at the expense of patch area and thus species—area limitations come into play, or ( iii ) using different indices of P and diversity, requires further investigation.…”
Section: Fire As a Driver Of Biodiversitymentioning
confidence: 97%
“…() also noted that species diversity should be greatest with a mixture of patches at different fire frequencies as the extremes were quite different in species composition (although any effect of patch size on S was not considered). Others have observed no effect (Davis et al, ) or a negative effect (Bassett et al, ; Foster et al, ). The extent to which this fails to support intermediate P as maximizing biodiversity due to ( i ) testing an inadequate range of P , thus observing only part of the ‘hump’, ( ii ) not using a fixed reference area, thus not appreciating that increasing patch type is at the expense of patch area and thus species—area limitations come into play, or ( iii ) using different indices of P and diversity, requires further investigation.…”
Section: Fire As a Driver Of Biodiversitymentioning
confidence: 97%
“…In the Murray Mallee, an examination of 21 species of invertebrates from key groups (psyllids, termites, scorpions, centipedes) in Triodia and Chenopod Mallee did not detect any species exhibiting a significant response across a 100year chronosequence (Avitabile, 2010). Many termite species nest in subterranean burrows and appear resilient to fire (Avitabile et al, 2015;Davis et al, 2018). In mallee vegetation of the Eyre Peninsula, South Australia, Teasedale et al (2013) found no difference in abundance between post-fire age classes for 15 orders of invertebrates; but, at a finer resolution, 17 morphospecies did show such variation.…”
Section: Animalsmentioning
confidence: 98%
“…We consider movements in relation to two broad classes of fire‐induced change: ( i ) abrupt changes that occur during and immediately following a fire, in which large amounts of biomass are incinerated, often resulting in radical changes in vegetation structure (Section II), and ( ii ) the longer‐term successional changes that occur in the period following fire (Sections III and IV), in which vegetation gradually returns in a process that can continue for decades or even centuries (Haslem et al ., ; Davis et al ., ). We consider how fire affects movement among habitat patches of differing fire histories that occur across a range of spatial and temporal scales (Fig.…”
Section: Introductionmentioning
confidence: 97%